Laurocerasus officinalis Roem. fruit extract induces cell death through caspase mediated apoptosis in gastric cancer cell lines - Karakaş, Nihal; Okur, Mehmet Evren; Öztunç, Nurşah; Polat, Derya Çiçek; Karadağ, Ayşe Esra (Walter de Gruyter GmbH, 2021)
Objectives: Laurocerasus officinalis Roem. fruits are traditionally used for several health problems. Although there are some studies about its antiproliferative effects on different cancer cells, no study was reported about its potential therapeutic efficacy against gastric cancers which is the most malignant disease in the digestive system with high morbidity and mortality. Methods: This study was aimed to evaluate L. officinalis fruit extract phytochemical contents as well as to compare anticancer effects on gastric cancer cells. The antioxidant activities were determined by ABTS and DPPH assays. Anticancer effects were measured by cell viability assays, then apoptotic proteins were analyzed by western blotting and flow cytometry. Results: Laurocerasus officinalis fruit methanol extract showed moderate antioxidant activity by ABTS(center dot) and DPPH center dot assays. Significant cytotoxic activities and caspase mediated apoptosis were detected in the extract treated MKN-45 and AGS gastric cancer cells respectively while sparing healthy cells. Conclusion: Our results showed that the L. officinalis Roem. extract has significant anticancer efficacy on gastric cancer cell lines; therefore, it can be further studied to determine its potential therapeutic components.

Giriş: Laurocerasus officinalis Roem. meyveleri halk arasında çeşitli sağlık problemlerine karşı kullanılmaktadır. Farklı kanser hücreleri üzerindeki antiproliferatif etkileri ile ilgili bazı çalışmalar olmakla birlikte, sindirim sistemindeki ciddi bir rahatsızlık olan, yüksek morbidite ve mortaliteye sahip mide kanserlerine karşı herhangi bir çalışma bildirilmemiştir. Yöntem: Bu çalışma L. officinalis meyve ekstrelerinin fitokimyasal analizi ile beraber karşılaştırmalı olarak mide kanseri hücrelerine karşı sitotoksik etkilerinin incelenmesini amaçlamıştır. Antioksidan aktivite ABTS ve DPPH yöntemleriyle araştırılmıştır. Antikanser etkinliği ise hücre canlılığı yöntemi ile araştırılmış ve sonrasında apoptotik proteinleri western blot ve flow sitometre yöntemleri ile ölçülmüştür. Sonuçlar: L. officinalis meyve metanol ekstresi, ABTS ve DPPH testlerine göre orta düzeyde antioksidan aktivite göstermiştir. Sağlıklı hücrelerde sitotoksik etki gözlemlenmezken, ekstre uygulanmış MKN-45 ve AGS mide kanseri hücrelerinde önemli sitotoksik aktiviteler ve kaspaz aracılı apoptoz saptanmıştır. Tartışma: Sonuçlar, L. officinalis Roem ekstresinin mide kanseri hücre hatları üzerinde önemli antikanser etkinliğine sahip olduğunu göstermiştir; bu nedenle, potansiyel terapötik bileşenlerini belirlemek için ileri çalışmalar gerçekleştirilebilecektir.
Laurocerasus officinalis Roem. meyve ekstrelerinin mide kanseri hücrelerinde kaspaz aracılı apoptoz yoluyla sitotoksik etkilerinin incelenmesi
Keywords: Antioxidant Activity; Apoptosis; Gastric Cancer; Laurocerasus Officinalis; Rosaceae; Antioksidan Aktivite; Apoptoz; Mide Kanseri; Laurocerasus Officinalis; Rosaceae